ACETYLCHOLINESTERASE INHIBITORY EFFECT OF 3-(1H-INDOL-3-YL)-1, 3-DIPHENYLPROPAN-1-ONE DERIVATIVES - KS, Manjunatha; Cp, Manu; Nd, Satyanarayan; Kn, Vinay; Ms, Vineetha; More S, Sunil (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of the study is acetylcholinesterase (AChE) inhibitory effect of 3-(1H-indol-3-yl)-1, 3-diphenylpropan-1-one derivatives by Ellman's method, physostigmine is used as positive control. Method: 3-(1H-indol-3-yl)-1, 3-diphenylpropan-1-one derivatives were synthesized by the addition of chalcone (0.25 g, 1 mmol), indole (0.12 g, 1 mmol) in ethanol (5 ml), and concentrated hydrochloric acid (5 mmol %). These earlier synthesized compounds were screened for AChE inhibitors by modifying Ellman's method. Results: Among the tested compounds, 3a and 3j were found to be having more potential than other compounds with half maximal inhibitory concentration values of 13.64 and 14.3 Î¼g/ml, respectively. Whereas, compounds 3c, 3e, 3g, and 3i exhibited an average AChE inhibition of 16.4, 17.9, 17.6, and 21.1 Î¼g/ml, respectively. Conclusion: The compounds 3-(1H-indol-3-yl)-1, 3-diphenylpropan-1-one derivatives were found to be possible lead molecules in AChE inhibition and even though, the molecules were structurally dissimilar to that of the standard, still they exhibited a considerable degree of inhibition and encourage the researchers to look into the mode of action of their inhibition ability against AChE.